Unlocking the power of optical imaging in the second biological window: Structuring near‐infrared II materials from organic molecules to nanoparticles. (22nd June 2021) - Dahal, Dipendra; Ray, Priyanka; Pan, Dipanjan
Abstract: Biomedical imaging techniques play a crucial role in clinical diagnosis, surgical intervention, and prognosis. Fluorescence imaging in the second biological window (second near‐infrared [NIR‐II]; 1000–1700 nm) has attracted attention recently. NIR‐II fluorescence imaging offers unique advantages in terms of reduced photon scattering, deep tissue penetration, high sensitivity, and many others. A host of materials, including small organic molecules, single‐walled carbon nanotubes, polymeric and rare‐earth‐doped nanoparticles, have been explored as NIR‐II emitting fluorescent probes. Efficient and viable approaches to design and develop fluorescence probes with tunable photophysical properties without compromising other key features are of paramount importance. Various chemical strategies are explored to increase the quantum yield of these imaging agents without compromising their spatiotemporal resolution, specificity, and tissue penetration capabilities. This review summarizes the strategies implemented to design and synthesize NIR‐II emitting nanoparticles and small organic molecule‐based fluorescent probes for applications in the biomedical field. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Implantable Materials and Surgical Technologies > Nanoscale Tools and Techniques in Surgery Abstract : Schematic representation of various materials used as theranostic agents in the NIR II biological window